Implementing Orton-Gillingham Method in Developing Application for Learning Hijaiyah Letters for Intellectual Disability Student: A Brief Analysis - ., Cahyana; Novi Dayawati, Cahyana; Ghufran, Muhammad; Fauzian, Fikri; Rasyidah, Khalimatu (International Journal of Engineering and Technology, 2019)
Hijaiyah (Arabic) letters are the letter of Al Qurâ€™an and the language of Shalat. It is crucial to be able to read Hijaiyah letters for moslem. Unfortunately, learning to read Arabic is not an easy task for intellectual disability students. Their special circumstance obstruct them in performing intellectual functioning, and they need distinctive approach. However, that is not the case in Indonesia. Teaching Hijaiyah letters is usually conducted in conventional approach, and there are few researches that propose alternative method. This paper discuss principles in developing application and implementing Orton-Gillingham (O-G) method for learning reading of Hijaiyah letters for intellectual disability student. O-G method is a multisensory approach for reading intervention that integrates VAKT modalities. Implementation will be made as learning application for smartphone for its mobility, accessibility and flexibility. The use of mobile application and O-G method provides diverse approach in learning Hijaiyah letters for intellectual disability student.Â